Asociación entre consumo de alimentos ultraprocesados y deterioro cognitivo - Benavides Salazar, Kevin Adrian (Machala : Universidad Técnica de Machala, 2024)
Introduction: Cognitive impairment, constitutes an important mental health problem, preventable. Within the etiology of this pathology is the lifestyle, being the food factor one of the most relevant, so in the present work it has been proposed to investigate the relationship between the intake of ultra-processed foods and cognitive impairment; these are foods with formulations of various ingredients such as preservatives and other additives that are intended to prolong the preservation of such foods. But it has been demonstrated that some additives provoke dysbiosis causing intestinal alterations thus affecting the intestine-brain microbiota axis causing the development of neurodegenerative diseases, temporary memory loss and behavioral changes in consumers. Objective: To identify ultra-processed foods related to the development of cognitive impairment through a literature review in high impact indexed journals. Methodology: A descriptive literature review was carried out in search of scientific articles published within the last 5 years in high impact journals such as ClinicalKey, PubMed, The New England Journal of Medicine and ScienceDirect. Conclusion: Additives alter the microbiota causing endocrine cells to release peptides, neuropeptides and enteric factors that influence the gut-brain microbiota axis, causing neuronal deterioration, Parkinson's, anxiety, Alzheimer's and many other pathologies. Therefore, it is of great importance to change the diet in order to stop the progression of cognitive impairment.
Introducción: El deterioro cognitivo, constituye un problema importante de salud mental, prevenible. Dentro de la etiología de esta patología está el estilo de vida, siendo el factor alimentación uno de los más relevantes, por lo que en el presente trabajo se ha propuesto investigar la relación entre la ingesta de alimentos ultraprocesados y deterioro cognitivo; estos son alimentos con formulaciones de varios ingredientes como preservantes y otros aditivos que tienen la finalidad prolongar la conservación de dichos alimentos. Pero se ha demostrado que algunos aditivos provocan disbiosis causando alteraciones intestinales afectando así el eje microbiota intestino – cerebro provocando el desarrollo de enfermedades neurodegenerativas, pérdida de la memoria temporal y cambios de comportamiento en los consumidores. Objetivo: Identificar los alimentos ultraprocesados relacionados con el desarrollo de deterioro cognitivos a través de la revisión bibliográfica en revistas indexadas de alto impacto. Metodología: Para el desarrollo del trabajo se realizó una revisión bibliográfica descriptiva, en busca de artículos científicos publicados dentro de los últimos 5 años en revistas de alto impacto como ClinicalKey, PubMed, The New England Journal of Medicine y ScienceDirect. Conclusión: Los aditivos alteran la microbiota haciendo que las células endocrinas liberen péptidos, neuropéptidos y factores entéricos que influyen sobre el eje microbiota intestino – cerebro, causando deterioro neuronal, Parkinson, ansiedad, Alzheimer y muchas otras patologías. Por lo es de gran importancia el cambio de dieta para poder detener el progreso de deterioro cognitivo.
Keywords: DISMINUCION COGNITIVA; ALIMENTOS ULTRAPROCESADOS; EJE CEREBRO E INTESTINO; MICROBIOMA INTESTINAL